Enterprise social policy as a means of development of social work (Verlag BARBARA BUDRICH, 2020)
Since its professional beginnings, social work has been a major actor and instrument of social policy. This study is a reconstruction of the development of social work in enterprises implemented as part of enterprise social policy in the territory of Bohemia and Moravia between the years 1876-1989. Using a hermeneutical approach based on historical research, the author explores the transformation of societal institutions, communities and structures.